2020
DOI: 10.3390/s20082386
|View full text |Cite
|
Sign up to set email alerts
|

Two-Electrode ECG for Ambulatory Monitoring with Minimal Hardware Complexity

Abstract: This article introduces a two-electrode ground-free electrocardiogram (ECG) with minimal hardware complexity, which is ideal for wearable battery-powered devices. The main issue of ground-free measurements is the presence of noise. Therefore, noise suppression methods that can be employed for a two-electrode ECG acquisition system are discussed in detail. Experimental measurements of a living subject and patient simulator are used to investigate and compare the performance of the three proposed methods utilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…External interferences such as AC mains near to a biopotential signal measurement system can capacitively couple current to the human body and to the measurement circuit [ 90 , 91 ]. Figure 16 depicts an ECG measurement system showing the coupling of currents from AC main lines to the human body and to the ECG measurement circuit.…”
Section: Biopotential Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…External interferences such as AC mains near to a biopotential signal measurement system can capacitively couple current to the human body and to the measurement circuit [ 90 , 91 ]. Figure 16 depicts an ECG measurement system showing the coupling of currents from AC main lines to the human body and to the ECG measurement circuit.…”
Section: Biopotential Sensingmentioning
confidence: 99%
“…The magnitude of this noise signal, , is proportional to the coupling currents, , , contact impedance of electrode-A ( ), contact impedance of electrode-B ( ) and their mismatches. can be calculated as follows [ 90 , 92 , 93 ]. …”
Section: Biopotential Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrode placed on the right leg provides the return path for common-noise reduction. This type of noise reduction is known as driven-right-leg (DRL) circuit [ 36 , 37 ]. Alternatively, the right leg electrode can be connected to the signal ground to reduce noise from the surroundings.…”
Section: Methodsmentioning
confidence: 99%
“…Several researchers demonstrated that three-electrode ECGs provide an approximately 98% and 74% sensitivity and specificity respectively for distinguishing between native and pathological heart electrical activity [7,8]. Branko Babusiak et al shown low powered two-electrode ECG system that may be used for the analysis of the electrical activity of the heart [9]. The three electrodes (lead-II) were used to acquire the ECG signal to monitor the electrical activity of the heart.…”
Section: Ecgmentioning
confidence: 99%